(1310)−4=
\( \left(\frac{10}{13}\right)^{-4}= \)
\( \left(\frac{10}{13}\right)^8= \)
\( \left(\frac{13}{19}\right)^7= \)
\( \left(\frac{1}{4}\right)^{-2}= \)
\( \left(\frac{1}{5}\right)^3= \)
\( \left(\frac{20}{21}\right)^4= \)
\( \left(\frac{2}{3}\right)^{-11}= \)
\( \left(\frac{2}{3}\right)^2= \)
\( \left(\frac{2}{3}\right)^a= \)
\( \left(\frac{2}{5}\right)^{-3}= \)
\( \left(\frac{2}{9}\right)^7= \)
\( \left(\frac{3}{4}\right)^x= \)
\( \left(\frac{3}{7}\right)^{-4}= \)
\( \left(\frac{3}{7}\right)^6= \)
\( \left(\frac{4}{7}\right)^3= \)
\( \left(\frac{4}{9}\right)^{-5}= \)
\( \left(\frac{5}{6}\right)^{10}= \)
\( \left(\frac{5}{8}\right)^9= \)
\( \left(\frac{6}{x}\right)^3= \)
\( \left(\frac{9}{20}\right)^6= \)